Przywództwo transformacyjne w dobie europejskich (r)ewolucji pokojowych = Transformational leadership at the time of european non-violent (r)evolutions - Korcz, Iwona (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
This article is devoted to the idea of transformational leadership within the context of European nonviolent revolutions. It comprises of three parts. The first one covers the idea of a revolution viewed as a sign of social change, but shown from both internal and external perspectives. There follows a discussion on various revolutions' concepts such as: behavioural, psychological, structural and political ones.
Keywords: transformacja; Europa